Journal of gay [and] lesbian social services : issues in practice, policy [and] research (New York: The Haworth Press)
"Fonds Suzan Daniel (FSD)Periodiciteit : ?Redactie : The Haworth Press, 10 Alice Street, Binghamton NY 13904-1580"